Pseudospin-dependent Acoustic Topological Insulator by Sonic Crystals With Same Hexagonal Rods - Jia, Ding; Gu, Shuai; Jiang, Shuai; Ge, Yong; Yuan, Shou-qi; Sun, Hong-xiang (Frontiers in Physics, 2021)
We report the experimental and numerical realization of a pseudospin-dependent acoustic topological insulator based on two sonic crystals constructed by the same regular hexagonal rods. Based on the zone folding mechanism, we obtain double Dirac cones with a four-fold deterministic degeneracy in the sonic crystal, and realize a band inversion and topological phase transition by rotating the rods. We observe the topologically protected one-way sound propagation of pseudospin-dependent edge states in a designed topological insulator composed of two selected sonic crystals with different rotation angles of the rods. Furthermore, we experimentally demonstrate the robustness of topological sound propagation against two types of defects, in which the edge states are almost immune to backscattering, and remain pseudospin-dependent characteristics. Our work provides a diverse route for designing tunable topological functional sound devices.